Analisis Produksi Biogas Terhadap Penambahan Kulit Singkong pada Variasi Campuran Limbah Cair Domestk dan Aquadest - Simare mare, Eva Malini; Sarah, Maya; Husin, Amir (Talenta Publisher (Universitas Sumatera Utara), 2022)
Domestic waste and agricultural food waste in the form of cassava peels have the potential as a source of raw material for making biogas. This research uses domestic waste from Wastewater Treatment Plant (WWTP) Cemara of Perusahaan Daerah Air Minum (PDAM) Tirtanadi, Sumatera Utara Province. The ratio of domestic waste inoculum from WWTP Cemara PDAM Tirtanadi and water in this study was 100:0, 70:30, 60:40, and 50:50 (v/v). Then, for each variation of the ratio, 3 kg of ground cassava peel was added. This study aims to determine the amount of biogas produced by measuring the pressure in a pipe connected to a bioreactor. The process of making biogas uses anaerobic fermentation with a batch system. The parameter tested in this study is the measurement of the Total Suspended Solid (TSS) value, Volatile Solid (VS) value, pH value, and total Chemical Oxygen Demand (COD) value. From the results of the research conducted, it was found that the variation in the ratio of 100:0 found biogas at a pressure of 205.8 Pa with TSS value of 1348 mg/L, VS value of 410 mg/L, pH value of 7.66 and COD value of 1088 mg/L.